PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) OLEH PLN UIP SUMBAGTENG CABANG SOEKARNO HATTA PADA PERUMAHAN BUMI TAMPAN LESTARI DI KOTA PEKANBARU - Septriana Rahmawati Ardiani; Evi Deliana; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
CSR is one of the obligations of companies, especially state-owned enterprises. The company's obligation to CSR as one of the manifestations of social solidarity or corporate concern for the community and environment. CSR has 4 forms, namely: Philantrophy Model of CSR, Economic View of CSR, Social Web Model of CSR and Integrative Model of CSR. In this case, researchers want to know the implementation of CSR by PLN UIP Sumbagteng on Bumi Tampan Lestari housing, considering two extra high voltage airway buildings located in residential areas.The method used in this research is sociological/ empirical. Data collection was carried out by the dissemination of questionnaires on 50 people who were respondents in the Bumi Tampan Lestari housing estate. In addition, data collection is also done by means of interviews and literature studies.The results stated that PLN only implements 2 (two) types of CSR, namely Philantrphy of CSR Model and Economic View of CSR. There are still two other types of CSR that have not been implemented by the PLN. in addition, the obstacles experienced by PLN Sumbagteng in the implementation of CSR consists of internal and external. Internally, obstacles are found such as leadership in the company and the size of the area that is the tangent of PLN UIP Sumbagteng. While from external such as local cultural environment and macroeconomic political environment.Therefore, PLN is expected to carry out CSR that has not been implemented. This aims to improve the quality of life of the community and the environment that benefits both the company itself, the local community and the community in general. In its implementation CSR is also the company's commitment to participate in sustainable economic development.Keywords: Corporate Social Responsibility - Company - PLN Sumbagteng